An engineering theory of creep of frozen soils - Ladanyi, B.; National Research Council of Canada. Division of Building Research (1972)
Most of the existing theories of creep have been developed from two different viewpoints: micromechanistic and macroanalytical. The former deal with events occurring at the atomic level and provide knowledge of the processes that control creep. The latter are based on certain macroscopic experimental findings and represent, in fact, an extension of the theory of plasticity to include time and temperature effects. Both the micromechanistic and macroanalytical approaches lead to fruitful results and each can benefit from the other. However, although the former has the advantage of being derived from physical concepts, the use of the latter is often preferred in practice if it provides basic relations that are broad in scope and can lead to improved procedures for designing structures. In this paper, a macroanalytical view of the problem of creep of frozen soils is presented. The proposed theory of creep has been developed mainly with the purpose of being used as a basis for solving a specific soil engineering problem, i.e., the bearing capacity of buried footings and anchors. Since the problem is itself rather complex, it was endeavoured to present the creep information in a relatively simple mathematical form. The theory, while using certain concepts and data from the frozen soils literature, follows more closely, nevertheless, the methods usual in certain engineering theories of creep of metals. La majorité des théories de fluage existantes ont été dé veloppées soit à partir d'un point de vue micro-mé canistique, soit à partir d'un point de vue macroanalytique. Les premières traitent des phénomènes se produisant à l'échelle atomique et tâchent d'expliquer des processus qui dirigent le fluage. Les dernières, par contre, sont basées sur certaines constatations expé rimentales macroscopiques et représentent, en effet, une extension de la théorie de la plasticité dans laquelle on tient compte des effets du temps et de la température. Les deux types de théories de fluage sont utiles en pratique et bénéficient l'une ...